2015
DOI: 10.4236/ijcm.2015.612122
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Laparoscopy in the Management of Female Infertility in Low Resource Countries: A Review of 208 Cases at the Yaoundé General Hospital, Cameroon

Abstract: Background: Infertility is a global problem, but the highest prevalence is in low resource countries, particularly in sub-Saharan Africa where tubal damage following pelvic infection is the commonest cause. Objectives: This study aimed to assess contribution of laparoscopy as a diagnostic and therapeutic tool in infertile women in our setting. Methods: A descriptive review of complete medical records of 208 women who underwent laparoscopy at the Gynaecology Unit of Yaoundé General Hospital from December 2007 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…This is similar to studies conducted by Bello et al [32]. This result is also similar to that of Kemfang et al [33] on the knowledge, attitudes and practices of Health Professionals on Breast Cancer at Yaoundé General Hospital, Cameroon. The fact that a significant proportion of the staff consider that cervical cancer screening can be done using cervical biopsy suggests a capacitybuilding of those healthcare professionals to biopsy technique, mostly those who are likely to receive patients during mass screening campaigns.…”
Section: Discussionsupporting
confidence: 92%
“…This is similar to studies conducted by Bello et al [32]. This result is also similar to that of Kemfang et al [33] on the knowledge, attitudes and practices of Health Professionals on Breast Cancer at Yaoundé General Hospital, Cameroon. The fact that a significant proportion of the staff consider that cervical cancer screening can be done using cervical biopsy suggests a capacitybuilding of those healthcare professionals to biopsy technique, mostly those who are likely to receive patients during mass screening campaigns.…”
Section: Discussionsupporting
confidence: 92%
“…This applies to surgical care but is particularly true for laparoscopic surgery which has been proven to be superior to traditional open surgery in terms of minimal perioperative morbidity, lower overall costs, better cosmesis, reduced blood lost, reduced postoperative pain and hospital stay duration, with consequent quick postoperative recovery [ 4 , 5 ]. Laparoscopy has been introduced in Cameroon in 1992 and is currently practiced in five public and eight private hospitals [ 6 - 11 ]. To the best of our knowledge, no study has evaluated the satisfaction of patients with the process of care during laparoscopic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The predominance of a female factor was seen in both primary and secondary infertility, but the female factor was significantly higher in secondary infertility than in primary infertility. This was explained by Ngowa et al, 6 where they suggested that pelvic infection resulting from ascending infection during childbirth can lead to tubal damage and thus higher contribution to the incidence in the female factors in secondary infertility.…”
Section: Discussionmentioning
confidence: 98%